INSTAGRAM DI KALANGAN MAHASISWA FIB UHO - Fikri Pratiwi; La Janu (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2018)
This study aims to determine the reasons for students to use instagram and analyze the meaning of instagram academically among UHO FIB students. The selection of informants in this study used a purposive sampling technique. Data collection techniques used in this study are field research techniques (field work) using two methods, namely observation involved (participation observation) and in-depth interviews (depth interview). This research is qualitative research and uses ethnographic research methods. The results showed that the use of Instagram among UHO FIB students had various reasons including: following trends, lifestyle (life style), having interesting features, useful content and as a means of socializing. Whereas the meaning of instagram in the academic world is inseparable from the three points of Tri Dharma College, namely: Education and Teaching, Research and Development, and Community Service. Keywords: instagram, Academic, student